STRATEGI PENGELOLAAN SAMPAH PADA DINAS LINGKUNGAN HIDUP DAN KEHUTANAN KOTA KENDARI - Nur Intan; Abdul Kadir; Rahman Tandi (Journal Publicuho, 2019)
This study used a descriptive qualitative research method with the technique of determining informants by purposive sampling. The technique of data collection is done by collecting primary data (interviews and observations) and collecting secondary data (literature studies and documentation). While the data analysis technique uses qualitative data analysis techniques.The results of this study indicate that the current waste management strategy at the Kendari City Environment and Forestry Service is quite maximal in overcoming waste generation. This can be seen from the strategic planning carried out by the Kendari City Environment and Forestry Service in the implementation of being able to increase the waste reduction target in carrying out its vision and mission of realizing Kendari which is clean and beautiful. While for operational planning at the Kendari City Environment and Forestry Service, it is still not optimal, it is faced with a related obstacle, namely the lack of technical staff available in their respective fields. This lack of a workforce can result in increasing volumes of waste every day because the population is not proportional to the number of employees, especially workers who handle the waste.